Clinical value of 18F-FDG PET/CT to predict MYCN gene, chromosome 1p36 and 11q status in pediatric neuroblastoma and ganglioneuroblastoma - Ren, Jiazhong; Fu, Zheng; Zhao, Yaqing (Frontiers in Oncology, 2023)
Objective: To explore the value of 18F-2-fluoro-2-deoxyglucose (FDG) positron emission tomography (PET) / computed tomography(CT) in MYCN gene and chromosome 1p36 and 11 statuses in newly diagnosed pediatric NB(neuroblastoma) and GNB(ganglioneuroblastoma). Methods: We retrospectively analyzed newly diagnosed patients with 48 NB and 12 with GNB. The data obtained from the clinical medical records included age, sex, pathologic type, and laboratory parameters such as lactate dehydrogenase (LDH), neuron-specific enolase (NSE) and the status of MYCN gene and chromosome 1p36 and 11q. The bone conditions were also obtained in the examination of bone marrow biopsy. Primary tumors were manually segmented to measure the maximum standardized uptake value (SUVmax), mean standardized uptake value (SUVmean), tumor volume(MTV) and total lesion glycolysis(TLG) and the maximal length of the lesion in the axial image(LEGmax). Results: The differences in bone marrow involvement and lymph node metastases in patients with chromosome 11q deletions were statistically significant (all p <0.05 ). Chromosome 11q deletion was an independent factor affecting bone marrow involvement (OR=17.796, p=0011). The levels of NSE, LDH, LEGmax and SUVmax, SUVmean, MTV, TLG all predicted MYCN gene amplification (all p < 0.05). The levels of LDH, LEGmax and MTV, TLG all predicted deletions in chromosomes 1p36 (all p < 0.05), while NSE, SUVmax and SUVmean did not (all p > 005). Conclusion: The levels of LDH, lesion LEGmax and TLG effectively predicted the status of the MYCN gene and chromosome 1p36. The chromosome 11q deletion is more likely to present with bone marrow involvement and lymph node metastases, indicating a worse progression-free survival.